An inventory of books and valuables in the Emperor's archive. Notes on a personal memorandum found among the papers of Henry VII of Luxembourg kept in Pisa. (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The article examines a hitherto unpublished document found among the charters of Emperor Henry VII that remained in Pisa after the sovereign's death (Pisa, Archivio Storico diocesano, Capitolo del Duomo, diplomatico, 1383 quater). The document, undated and drafted in the first person, contains a list of books and goods deposited in Toul, Basel and Ivrea by an anonymous member of Henry VII's entourage, presumably on the stages of a journey to join the King of the Romans in Italy. The reconstruction of the travel itinerary and the author's personal library (consisting of works of a mainly theological nature, including numerous writings by Thomas Aquinas) brings to light a prominent member of the imperial retinue, whom we propose to identify as Johannes de Lucidomonte (Johannes Picardi of Lichtenberg).
Keywords: Emperor Henry VII of Luxemburg; history of medieval libraries; Dominicans; travels and mobility; inventories; Thomas Aquinas